Cochlear Implantation in the Setting of Menière's Disease After Labyrinthectomy: A Meta-Analysis. Issue 8 (September 2021) - Selleck, Anne Morgan; Dillon, Margaret; Perkins, Elizabeth; Brown, Kevin D.
Abstract : Objective: Characterize the speech recognition and sound source localization of patients with unilateral Menière's disease who undergo labyrinthectomy for vertigo control with simultaneous or sequential cochlear implantation. Databases Reviewed: PubMed, Embase, and Cochrane databases. Methods: The search was performed on May 6, 2020. The keywords utilized included: "Menière's disease AND cochlear implant;" "cochlear implant AND single sided deafness;" "cochlear implant AND vestibular;" and "labyrinthectomy AND cochlear implant." Manuscripts published in English with a publication date after 1995 that assessed adult subjects (≥18 years of age) were included for review. Subjects must have been diagnosed with Menière's disease unilaterally and underwent labyrinthectomy with simultaneous or sequential cochlear implantation. Reported outcomes with cochlear implant (CI) use included speech recognition as measured with the consonant-nucleus-consonant (CNC) word test and/or sound source localization reported in root-mean squared (RMS) error. The method of data collection and study type were recorded to assess level of evidence. Statistical analysis was performed with Wilcoxon signed ranks test. Results: Data from 14 CI recipients met the criteria for inclusion. Word recognition comparisons between the preoperative interval and a postactivation interval demonstrated a significant improvement with the CI ( p = 0.014), with an average improvement of 23% (range −16 to 50%). Sound source localization postoperatively with the CI demonstrated an average RMS error of 26° (SD 6.8, range 18.7–43.1°) compared to the 42° (SD 19.1, range 18–85°) in the preoperative or CI off condition, these two conditions were not statistically different ( p = 0.148). Conclusion: Cochlear implantation and labyrinthectomy in adult patients with Menière's disease can support improvements in speech recognition and sound source localization for some CI users, though observed performance may be poorer than traditional CI candidates.